The sound of study: Student experiences of listening in the university soundscape. Issue 6 (1st November 2016) - Thoutenhoofd, Ernst D.; Knot-Dickscheit, Jana; Rogge, Jana; van der Meer, Margriet; Schulze, Gisela; Jacobs, Gerold; van den Bogaerde, Beppie
Abstract : The students from three universities (Groningen, Oldenburg and the University of Applied Sciences in Utrecht) were surveyed on the experience of hearing and listening in their studies. Included in the online survey were established questionnaires on hearing loss, tinnitus, hyperacusis, a subscale on psychosocial strain resulting from impaired hearing and a questionnaire about students' perceptions of listening ease in study environments. Results from the 10, 466 students who completed the survey (13% response rate) are highlighted, with particular attention to listening ease and measures proposed by students for improving it. The number of students having problems with hearing and listening transpires to be substantially larger when research is not constrained to students with a recognised hearing impairment, suggesting that listening is primarily a sociocultural performance and achievement rather than an artefact of physical attributes. One finding from our survey is that classroom practices could be more effective if study soundscapes are improved, while universities might exercise greater inclusive responsibility for study as a high quality sensory experience for the benefit of all students.